Improvement of rodent pest control strategy: II - Response of wild brown rats to baits containing preservative previously exposed to unfavourable environmental conditions - Blažić, Tanja; Đurović-Pejčev, Rada; Đorđević, Tijana; Jovičić, Ivana; Međo, Irena; Stojnić, Bojan; Jokić, Goran (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
Control of brown rats (Rattus norvegicus) is an indispensable measure of protection of human population and domestic animals, aimed at preventing the spread of infectious diseases, and a measure of protection of goods and commodities that the brown rat can damage by its presence and activities. Rodent control procedures in environments with unfavourable conditions, such as high temperature and humidity, may fail due to reduced bait palatability caused by its degradation. Baits were prepared based on OEPP/ EPPO recommendations, while ECHA recommendation was followed for bait exposure to unfavourable environmental conditions. Placebo baits were prepared by mixing ground maize grain and paraffin. Test baits, made by mixing the placebo bait with sorbic acid, were exposed to unfavourable environmental conditions (temperature 30-35 ⁰C and humidity 90-95%). Brown rats previously captured from a wild population were used as the test organism. After an acclimation period, the animals were subjected to a four-day choice feeding test in which they were simultaneously offered placebo and test baits. The average bait palatability was unchanged, and the palatability of bait containing the preservative was 48.85 %. Furthermore, the preservative had no influence on bait consumption, compared to baits in the pre-test period, as there was no statistical difference in total amounts of bait consumed in the tests. The results indicate that 1% sorbic acid can be used as a potentially good additive to baits that are planned to be used in sewage systems and other areas where unfavorable environmental conditions prevail and there is a risk of rapid mold development and bait decay.